Hands percussion : moving towards a Malaysian identity / Jotsna Nithyanandan - Nithyanandan, Jotsna (2015)
This study examined the idea behind the compositions of Malaysian Chinese Shigu drumming performing group Hands Percussion (HANDS) that have incorporated Gamelan, and the Indian Tabla drumming patterns as part of their repertoire. HANDS began with the 24 Seasons Drums, when it was founded in 1997, as a Malaysian Chinese percussion ensemble. This dissertation elucidates how HANDS later forms a multi-ethnic identity in its production that moved away from a single ethnic Chinese performing art group. This study touches on issues of culture and intercultural exchanges on the premise that HANDS is based in Malaysia, a country that is pluralistic and multicultural and how this in turn influences the creative process of HANDS composer and founder, Bernard Goh and guest composer, Susan Sarah John. It will also look at the process involving the composition of pieces such as these, and an enquiry into the poeisis stage of the composers. Past literatures on Malaysian music focused extensively on indigenous genres that are mostly singular in their ethnic basis. This research identifies new scholarship into a multi-ethnic context and identity as a Malaysian music-making process. Methodology involves fieldwork, performance analysis, video and recording analysis, interview and transcription. The outcome of this research shows the music-making process of HANDS and its portrayal of a Malaysian identity.